مستوى الرصيد اللغوي لدى حفظة القرآن الكريم: دراسة ميدانية على تلاميذ المرحلة الابتدائية - شرياف، زهرة Sheriaf, Zahrah (جامعة عمار ثليجي بالأغواط - كلية العلوم الاجتماعية, 2023)
هدفت الدراسة إلى دراسة الرصيد اللغوي لدى تلاميذ السنة الخامسة ابتدائي الحافظين للقرآن الكريم، تكونت عينة الدراسة من حالتين تحفظان القرآن الكريم بمدرسة الأمير عبد القادر بيوب سعيدة، تم استخدام المنهج العيادي وتقنيتي المقابلة والملاحظة، إضافة إلى اختيار T.L.P خاص بقياس الرصيد اللغوي عند الطفل والمكون من أربعة اختبارات، الاختبار الأول خصص لتسمية والوصف والثاني أدوات الظرف وأدوات الشرط والاستثناء والاختبار الثالث خصص للضمائر وأخيرا اختبار الخاص بالإعراب وتم معالجة المعطيات والبيانات إحصائيا باستخدام النسب المئوية. وخلصت النتائج إلى: 1-لحفظة القرآن الكريم بالنسبة لتلاميذ الخامسة ابتدائي رصيد لغوي ثري على مستوى التسمية والوصف. 2-لحفظة القرآن الكريم بالنسبة لتلاميذ الخامسة ابتدائي رصيد لغوي ثري على مستوى أدوات الظرف وأدوات الشرط والاستثناء. 3-لحفظة القرآن الكريم بالنسبة لتلاميذ الخامسة ابتدائي رصيد لغوي ثري على مستوى الضمائر. 4-لحفظة القرآن الكريم بالنسبة لتلاميذ الخامسة ابتدائي رصيد لغوي ثري على مستوى الإعراب. نستنتج من خلال ما تحصلنا عليه في الدراسة التطبيقي أن لحظة القرآن الكريم رصيد لغوي متنوع وهذا ما يعكس الأثر الإيجابي للقرآن الكريم. Holy Qur’an. The study sample consisted of two cases who memorized the Holy Qur’an at Prince Abdel Qadir youb Saeed School. Clinical approach and interview and observation techniques were used, in addition to choosing T.L. P is concerned with measuring the linguistic balance of the child, which consists of four tests. The first test is devoted to naming and description, the second is adverb tools, conditional and exception tools, the third test is devoted to pronouns, and finally the test for parsing, the data and data were processed statistically using percentages. The results concluded: 1- The memorizers of the Noble Qur’an for the fifth primary school students have a rich linguistic balance at the level of nomenclature and description. 2- For the memorizers of the Noble Qur’an for the fifth elementary students, a rich linguistic balance at the level of adverbial tools, conditional tools and exceptions. 3- For memorizers of the Noble Qur’an for the fifth graders, a rich linguistic balance at the level of pronouns. 4- For memorizers of the Noble Qur’an for the fifth graders, a rich linguistic balance at the level of syntax. We conclude through what we obtained in the applied study that the moment of the Holy Qur’an is a diverse linguistic balance, and this reflects the positive impact of the Holy Qur’an.
Keywords: الرصيد اللغوي -- التعليم الابتدائي -- المهارات اللغوية -- حفظة القرآن -- الجزائر